What Makes Community-based Physical Activity Programs for Culturally and Linguistically Diverse Older Adults Effective? A Systematic Review - Montayre, J; Neville, S; Dunn, I; Shrestha-Ranjit, J; Wright-St Clair, V (Wiley, 2020)
OBJECTIVE: This integrative review aimed to determine the features of effective physical activity programs for culturally and linguistically diverse (CALD) older adults. METHODS: We searched for relevant articles in MEDLINE, PubMed, Google Scholar, Scopus and CINAHL. Articles were selected for evaluation if they included CALD older adults and implemented physical activity programs with culturally specific design features. Consistent with the Whittemore and Knafl integrative review methodology, we used the Downs and Black Checklist, Mixed Methods Appraisal Tool and the McMaster University appraisal tool for quantitative studies to assess the quality of included articles. RESULTS: Seven articles were included in this review. Effective community-based exercise or physical activity programs for CALD populations commonly featured close-to-home delivery, native language instruction and adaptations of culturally familiar activities. CONCLUSION: The provision of culturally appropriate community-based physical activity programs appears to support and encourage engagement among CALD older adults.
Keywords: CALD; Culturally appropriate interventions; Exercise program; Integrative review